Analisis Baitul Maal Wat Tamwil (BMT) Perspektif Al- Qur’an - Mohammad Idil Ghufron; Rohma Dewi (Nurul Jadid University, 2023)
This study intends to analyze aspects of baitul maal wat tamwil (bmt) from the perspective of the Koran. This study uses qualitative research. The type of data in this research uses secondary data sourced from the Qur'an, Hadith, books, and journals as references. The development carried out is to modify the BMT that researches in the field to become BMT according to the perspective of the Koran. Another development is that we know each of the differences between the BMT in the field and the word of God. The next development is to determine whether BMT has been explained in the Qur'an or not. Other developments also add knowledge constructs about Islamic banking to conventional banks. This study has a qualitative approach. Determining the number of samples in this study adjusted to the snowball sampling technique. The data collection technique in this study was the technique of taking data sources, which at first were small in number and then enlarged. This was because the small data sources had not been able to provide satisfactory data, so looking for other informants who were used as data sources.